Letter from Fritz Boas to Max Bredig, September 1937 - Boas, Fritz (1937)
Fritz Boas writes to Max Albert Bredig (1902-1977) about needing approval from the military registration office before emigrating from Germany. Starting in 1937, stricter emigration policies were put in place. In order to emigrate from Germany, Jewish people had to have documents that certified they had no outstanding debts to the country, a passport, a formal dissolution of residence, approval from the Reich Ministry of Finance, and a customs declaration.
Keywords: Emigration and immigration; Bredig, Max Albert, 1902-1977; Boas, Fritz; Draft; Third Reich